Visible light-photoreactive composite surfaces with thermoresponsive wetting and photocatalytic properties - László Mérai; Ágota Deák; Balázs Szalai; Gergely Ferenc Samu; Gábor Katona; László Janovák (eXPRESS Polymer Letters)
With the increasing demand for liquid manipulation and microfluidic techniques, surfaces with external stimuli induced real-time tunable wetting properties are getting into the focus of materials science research. In this study, we present poly(dimethylsiloxane) (PDMS) copolymer-based composite coatings with thermally adjustable wetting and visible-light photoreactivity. To give thermal responsivity to the spray-coated or doctor blade-casted PDMS surfaces, they were grafted with poly(N-isopropylacrylamide) (PNIPAAm), applying the Activators Regenerated by Electron Transfer – Atom Transfer Radical Polymerization (ARGET-ATRP) method. As the lower critical solution temperature (LCST) of the grafted PNIPAAm chains appeared to be 34°C, the copolymer films showed thermoresponsive, and PNIPAAm surface concentration-dependent wetting characteristics. The addition of 15 wt% visible light-active plasmonic Ag-TiO2 photocatalyst nanoparticles (dprimary ~50 nm) enriched the coatings with photocatalytic activity, which was also proven to be temperature-dependent during methylene-blue (MB; c0 = 6.25 mM) photodegradation tests (blue LED-light, λ = 405 nm) at the S/L-interface. Thanks to the real-time tunable wetting and photocatalytic properties, the presented coatings may offer a novel route towards sophisticated liquid manipulation.